Glucose Tolerance in Pregnant Women Inflicted with Candida Albicans - AL-Khayat, Tarik Hovthy A.T.; AL-Mulla, Fatma Haider K. (AL-Kindy College Medical Journal, 2009)
Background: Many previous studies were concerned withthe relationship between gestational diabetes and thedevelopment of vaginal candidiasis in pregnant women. Inthis study, our aim is directed to uncover glucose tolerancestatus in non-diabetic pregnant women inflicted withcandida albicans.Methods: Thirty-four pregnant women with vaginalcondidiasis (as demonstrated by microscopy) were enrolledin this study. The patients were nearly similar in theiranthropometric and demographic criteria with those of thehealthy pregnant women (control group, forty –twowomen). Fasting plasma sugar and glucose tolerance testwere alone for all patients and control group.Results: fasting plasma sugar was significantly higher inthe candidiasis-positive pregnant women in comparison tothose of candidiasis-negative subjects (5.09 mmol/L vs.4.71, p